Analisis Efektivitas Penerimaan Pajak Reklame Terhadap Pendapatan Asli Daerah Kota Tangerang Selatan Tahun 2019 - 2021 - UTSMAN SAEPUDIN; Ambarwati Ambarwati (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
This study aims to discuss the effectiveness of Advertising Tax Revenue on the Real Regional Income of South Tangerang City. The main problem in this study is how the level of effectiveness of Advertising Tax Revenue on Real Regional Income. This study was conducted at the Regional Rvenue Board of South Tangerang City using a descriptive approach and data collection techniques of interviews and documentation where the researcher calculated the effectiveness of Advertising Tax Revenue on Real Regional Income. In order to find out the actual situation, Researchers conducted interviews with several parties. Based on the results of the study, from 2019-2021 the effectiveness of Advertising Tax receipts has not been effective. The contributing factors are the awareness of the taxpayer in extending the advertisement tax period, the lack of knowledge of the taxpayer and the process of paying the advertisement tax which is quite time consuming.